Intravenous tPA (Tissue-Type Plasminogen Activator) Correlates With Favorable Venous Outflow Profiles in Acute Ischemic Stroke. Issue 10 (23rd June 2022) - Faizy, Tobias D.; Mlynash, Michael; Marks, Michael P.; Christensen, Soren; Kabiri, Reza; Kuraitis, Gabriella M.; Broocks, Gabriel; Winkelmeier, Laurens; Geest, Vincent; Nawabi, Jawed; Lansberg, Maarten G.; Albers, Gregory W.; et al.
Abstract : Background: Intravenous tPA (tissue-type plasminogen activator) is often administered before endovascular thrombectomy (EVT). Recent studies have questioned whether tPA is necessary given the high rates of arterial recanalization achieved by EVT, but whether tPA impacts venous outflow (VO) is unknown. We investigated whether tPA improves VO profiles on baseline computed tomography (CT) angiography (CTA) images before EVT. Methods: Retrospective multicenter cohort study of patients with acute ischemic stroke due to large vessel occlusion undergoing EVT triage. Included patients underwent CT, CTA, and CT perfusion before EVT. VO profiles were determined by opacification of the vein of Labbé, sphenoparietal sinus, and superficial middle cerebral vein on CTA as 0, not visible; 1, moderate opacification; and 2, full. Pial arterial collaterals were graded on CTA, and tissue-level collaterals were assessed on CT perfusion using the hypoperfusion intensity ratio. Clinical and demographic data were determined from the electronic medical record. Using multivariable regression analysis, we determined the correlation between tPA administration and favorable VO profiles. Results: Seven hundred seventeen patients met inclusion criteria. Three hundred sixty-five patients received tPA (tPA+), while 352 patients were not treated with tPA (tPA−). Fewer tPA+ patients had atrial fibrillation (n=128 [35%] versus n=156 [44%]; P =0.012) and anticoagulants/antiplatelet treatment before acute ischemic stroke due to large vessel occlusion onset (n=130 [36%] versus n=178 [52%]; P <0.001) compared with tPA− patients. One hundred eighty-five patients (51%) in the tPA+ and 100 patients (28%) in the tPA− group exhibited favorable VO ( P <0.001). Multivariable regression analysis showed that tPA administration was a strong independent predictor of favorable VO profiles (OR, 2.6 [95% CI, 1.7–4.0]; P <0.001) after control for favorable pial arterial CTA collaterals, favorable tissue-level collaterals on CT perfusion, age, presentation National Institutes of Health Stroke Scale, antiplatelet/anticoagulant treatment, history of atrial fibrillation and time from symptom onset to imaging. Conclusions: In patients with acute ischemic stroke due to large vessel occlusion undergoing thrombectomy triage, tPA administration was strongly associated with the presence of favorable VO profiles.